Coating liquid, and method for manufacturing solid-state battery by coating positive electrode active material
Patent Information
- Application Number
- CN202512015483.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-28
- Filing Date
- 2025-12-30
- Publication Date
- 2026-10-30
AI Technical Summary
[0025]根据本发明,能够提供一种能够抑制伴随电池的充放电的包覆正极活性物质的电阻增加的涂层液。
Smart Images

Figure CN123017967A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a coating liquid, a method for manufacturing a positive electrode active material, and a method for manufacturing a solid-state battery. Background Technology
[0002] Various techniques have been proposed for coating positive electrode active materials as disclosed in Patent Documents 1-2.
[0003] Patent Document 1: Japanese Patent Application Publication No. 2023-122182
[0004] Patent Document 2: Japanese Patent Application Publication No. 2023-136753 Summary of the Invention
[0005] Previously, various methods of coating positive electrode active material particles have been proposed. This is because if the sulfide solid electrolyte comes into direct contact with the positive electrode active material, the sulfide solid electrolyte may degrade. For example, coating positive electrode active materials can be manufactured by forming a coating film on the surface of the positive electrode active material particles using a coating solution.
[0006] Patent document 1 describes the following: In the coating liquid, the presence ratio of units formed by the polymerization of phosphoric acid units such as dimers (P2O7) with PO4 units or chain condensed phosphoric acid is large, forming a coating film with high coverage and thinness.
[0007] However, with repeated charge-discharge cycles, the resistance of the previously coated positive electrode active material sometimes increases. This is believed to be because there is room for improvement in the coating efficiency of the coated positive electrode active material.
[0008] The present invention was made in view of the above-mentioned actual situation, and its main objective is to provide a coating liquid that can suppress the increase in resistance of the positive electrode active material during the charging and discharging of the battery.
[0009] That is, the present invention includes the following methods.
[0010] <1> A coating liquid containing a solvent and a solute comprising a phosphoric acid compound, wherein,
[0011] The coating liquid exhibits a Raman spectrum at 980 cm⁻¹. -1 Nearby and 1025cm -1 Peak values are found in the vicinity.
[0012] <2> According to the coating liquid described in <1>, wherein,
[0013] The coating liquid contains Li and B, and the coating liquid is in the 1025cm... -1 Peak area I near the peak 1025 Relative to the 980cm-1 Peak area I near the peak 980 The ratio (I) 1025 / I 980 () in the range of 0.3 and above and 8.8 and below.
[0014] <3> The coating liquid according to <1> or <2>, wherein,
[0015] The phosphoric acid compound includes an acidic hexametaphosphate compound.
[0016] <4> A method for manufacturing a coated positive electrode active material, wherein,
[0017] The manufacturing method includes the following steps:
[0018] The mixture is prepared by mixing positive electrode active material particles and the coating liquid described in any one of <1> to <3>; and
[0019] The coated positive electrode active material is manufactured by drying the mixture.
[0020] The coated positive electrode active material comprises positive electrode active material particles and a coating film.
[0021] The coating film covers at least a portion of the surface of the positive electrode active material particles.
[0022] <5> A method for manufacturing a solid-state battery, the solid-state battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, the method for manufacturing the solid-state battery comprising the following steps:
[0023] The positive electrode layer is formed in a layered manner as a positive electrode composite material containing at least the positive electrode active material obtained by the manufacturing method described in <4>.
[0024] Invention Effects
[0025] According to the present invention, a coating liquid capable of suppressing the increase in resistance of the positive electrode active material during the charging and discharging of the battery can be provided. Attached Figure Description
[0026] Figure 1 These are the Raman spectra of the coating liquids of Examples 1-3 and Comparative Example 1. Detailed Implementation
[0027] The following describes embodiments based on the present invention. Furthermore, aside from matters specifically mentioned in this specification, things necessary for implementing the present invention (e.g., the general structure and manufacturing process of the coating liquid of the present invention are not characterized) can be understood by those skilled in the art based on prior art. The present invention can be implemented based on the disclosure in this specification and common technical knowledge in the field.
[0028] In this invention, unless otherwise specified, the average particle size is the particle size at 50% of the cumulative value of the particle size distribution of the volume reference determined by laser diffraction-scattering particle size distribution measurement, i.e., the median particle size (D50).
[0029] 1. Coating liquid
[0030] In this invention, a coating liquid is provided, which contains a solvent and a solute comprising a phosphoric acid compound, wherein the coating liquid exhibits a Raman spectrum at 980 cm⁻¹. -1 Nearby and 1025cm -1 Peak values are found in the vicinity.
[0031] In this invention, 980cm -1 Nearby refers to 980±5cm -1 Within the range.
[0032] In this invention, 1025cm -1 Nearby refers to 1025±5cm -1 Within the range.
[0033] In Raman spectroscopy, 980 cm⁻¹ -1 The nearby peak is estimated to originate from P3O 10 5- (Metaselic acid unit), 1025 cm -1 The nearby peak is estimated to originate from P2O7. 4- (Pyrophosphate unit). Phosphoric acid compounds can take on various forms in the coating solution, thus the coating solution contains various phosphate units. This invention is based on the novel insight that by using a coating solution containing both metaphosphoric acid units (polymerized from three PO4 units) and pyrophosphate units (polymerized from two PO4 units), it is possible to obtain a coated positive electrode active material with high coating film coverage and low resistance increase rate during battery charge-discharge cycles. The crystallization ease differs between the metaphosphoric acid and pyrophosphate units, presumably because the presence of both units in the coating solution results in a coating film with a mixture of amorphous and crystalline structures. It is believed that in coating positive electrode active materials, a coating film with a mixture of amorphous and crystalline structures is important for balancing increased coverage and reduced resistance increase rate.
[0034] In this invention, the Raman spectrum of the coating liquid is determined by Raman spectroscopy. The determination conditions are as follows.
[0035] (Measurement conditions)
[0036] Laser unit wavelength: 532nm
[0037] Laser energy: 1.4mW
[0038] • Exposure time: 40Hz
[0039] • Number of scans: 100
[0040] As a measuring device, for example, the DXR3xi imaging micro Raman spectroscopy manufactured by Thermo Fisher Scientific Inc. can be used.
[0041] From the viewpoint of improving the coating efficiency and reducing the rate of increase in resistance, in the coating liquid of the present invention, 1025 cm -1 Peak area I near the peak 1025 Compared to 980cm -1 Peak area I near the peak 980 The ratio (I) 1025 / I 980 The value can be above 0.3, above 1.0, above 1.2, below 10.0, or below 8.8. The above ratio (I) 1025 / I 980 It can be in the range of 0.3 or higher and 8.8 or lower.
[0042] Regarding the ratio of peak area (I) 1025 / I 980 ), capable of connecting 980cm in the Raman spectrum of the coating liquid. -1 Draw the baseline at both ends of the nearby peak and calculate the peak area I. 980 and connection 1025cm -1 Draw the baseline at both ends of the nearby peak and calculate the peak area I. 1025 To calculate.
[0043] The coating liquid of the present invention contains a solvent and a solute comprising a phosphoric acid compound.
[0044] As a solvent, there are no particular limitations as long as it can dissolve the solute. Specific solvents include, for example, water and alcohol. For water, ion-exchanged water can be used, for example.
[0045] Phosphoric acid compounds included as solutes only need to be soluble in the solvent to obtain a Raman spectrum with a wavelength of 980 cm⁻¹. -1 Nearby peaks and 1025cm-1 The coating liquid containing phosphoric acid compounds near the peak can be used. That is, as a phosphoric acid compound, it is possible to use a solution that dissolves in a solvent to generate P3O. 10 5- (Metaselic acid unit) and P2O7 4- Any phosphoric acid compound of (pyrophosphate unit). Only one phosphoric acid compound may be used, or two or more may be used in combination. Specific examples of phosphoric acid compounds include tripolyphosphate compounds, metaphosphate compounds, and acidic hexametaphosphate compounds.
[0046] Phosphoric acid compounds can be salts such as sodium salts; for example, sodium tripolyphosphate and acidic sodium hexametaphosphate can also be used as phosphoric acid compounds. By including sodium in the coating solution, it is expected that the stability of the polymer structure of the phosphoric acid units will be improved. It is speculated that, from the viewpoint of improving the coating film formed by the coating solution, the polymer structure of the phosphoric acid compound is important. Therefore, it is believed that by improving the stability of the polymer structure, a coated positive electrode active material with a high coating efficiency can be obtained.
[0047] In this invention, the phosphoric acid compound can be an acidic hexametaphosphate compound such as sodium hexametaphosphate. As a phosphoric acid compound, a coating solution containing an acidic hexametaphosphate compound is expected to improve not only the coating efficiency and resistance increase rate, but also reduce the initial resistance of the coated positive electrode active material.
[0048] In this invention, the phosphate unit can include various variations. For example, the -OH group can dissociate, and H can be replaced by other elements, such as -OLi and -ONa.
[0049] The content of phosphoric acid compound in the coating liquid is not particularly limited. For example, relative to 100 parts by mass of solvent, it can be 0.1 to 15.0 parts by mass, 1.0 to 10.0 parts by mass, or 1.0 to 5.0 parts by mass.
[0050] The coating liquid of the present invention may contain boron (B). There are no particular limitations on the boron compound used as the source of B; for example, boric acid can be used. Boric acid may be metaboric acid, or any other type of boric acid.
[0051] The content of boron (B) in the coating solution is not particularly limited. For example, the amount of boron (B) is C. B Mass C relative to phosphorus (P) P The ratio (C) B / C P The value can be above 0.1, above 0.8, above 1.0, below 1.5, or below 1.2.
[0052] The coating liquid of the present invention may contain Li (lithium). Examples of lithium compounds that can be used as Li sources include lithium hydroxide, lithium carbonate, and lithium nitrate.
[0053] The content of Li in the coating solution is not particularly limited. For example, the amount of lithium (Li) is C. Li Mass C relative to phosphorus (P) P The ratio (C) Li / C P The value can be 1.0 or higher, 1.5 or higher, 1.8 or higher, or below 2.5 or below 2.0.
[0054] The coating liquid of the present invention may contain B and Li. In the coating liquid, the amount of lithium (Li) is C. Li Mass C relative to phosphorus (P) P The amount of boron (B) C B The ratio of the total amount [C] Li / (C P +C B For example, it can be above 0.5, above 0.7, above 0.9, below 1.2, or below 1.0.
[0055] The coating liquid of the present invention can be used to form a coating film when manufacturing a coating film containing positive electrode active material particles and a coating material covering at least a portion of the surface of the positive electrode active material particles.
[0056] 2. Manufacturing method for coating positive electrode active material
[0057] In this invention, a method for manufacturing a coated positive electrode active material is provided, comprising the following steps: preparing a mixture by mixing positive electrode active material particles and the coating liquid of the present invention described above; and manufacturing the coated positive electrode active material by drying the mixture, wherein the coated positive electrode active material comprises the positive electrode active material particles and a coating film, and the coating film covers at least a portion of the surface of the positive electrode active material particles.
[0058] According to the manufacturing method of the coated positive electrode active material of the present invention, it is possible to obtain a coated positive electrode active material with high coating film coverage and suppressed resistance increase even after repeated charge and discharge.
[0059] The method for manufacturing the coated positive electrode active material of the present invention includes the step of preparing a mixture by mixing positive electrode active material particles and the coating liquid of the present invention. Regarding the coating liquid, due to the above, a description is omitted here.
[0060] Examples of positive electrode active material particles that serve as the core for coating the positive electrode active material include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(NiCoMn)O2, Li(NiCoAl)O2, and LiFePO4. Here, "(NiCoMn)" in "Li(NiCoMn)O2" indicates that the total composition ratio within the parentheses is 1; as long as the total is 1, the composition ratio of each element is arbitrary. For example, Li(NiCoMn)O2 could be Li(Ni1 / 3Co...) 1 / 3 Mn 1 / 3 O2, Li (Ni) 0.5 Co 0.2 Mn 0.3 O2, Li (Ni) 0.8 Co 0.1 Mn 0.1 In "Li(NiCoAl)O2", "(NiCoAl)" indicates that the total composition ratio within the parentheses is 1. As long as the total is 1, the composition ratio of each element is arbitrary. For example, Li(NiCoAl)O2 can be Li(Ni... 0.81 Co 0.15 Al 0.04 O2, etc.
[0061] The positive electrode active material particles can be an aggregate of primary particles, i.e., secondary particles. When the positive electrode active material particles are secondary particles, for example, D50 can be 1–50 μm or 5–15 μm. The maximum Ferri radius of the primary particles of the positive electrode active material can be, for example, 0.1–3 μm.
[0062] The mixture of positive electrode active material particles and coating liquid can be a suspension (slurry) or a wet powder. For example, a suspension can be prepared by dispersing positive electrode active material particles (powder) in the coating liquid, or a wet powder can be formed by spraying the coating liquid onto the positive electrode active material particles (powder). In the preparation of the suspension or the formation of the wet powder, any mixing device, granulation device, etc., can be used.
[0063] The method for manufacturing the coated positive electrode active material of the present invention includes the step of drying the above-mentioned mixture. By drying the mixture, a coating film is formed on the surface of at least a portion of the positive electrode active material particles. The drying method for the mixture is not particularly limited, and known methods can be used.
[0064] As a specific drying method, spray drying can be cited as an example. In spray drying, while spraying a suspension containing a coating liquid and positive electrode active material particles from a nozzle, the coating liquid is dried with hot air, and the positive electrode active material particles are coated with a coating film. In spray drying, the solid content concentration of the suspension can be, for example, 1–80%, or 30–75%. The nozzle diameter can be, for example, 0.1–10.0 mm, or 0.1–1.0 mm. The hot air temperature can be, for example, 100–200°C. The air supply volume can be 0.40–0.50 m³ / h. 3 / min, or 0.45m 3 / min.
[0065] The positive electrode active material can be coated by heat treatment. For example, the heat treatment temperature can be 150–300°C or 200°C, and the heat treatment time can be 1–10 hours or 5 hours. The heat treatment atmosphere can be, for example, atmospheric atmosphere or an inactive atmosphere.
[0066] In the coated positive electrode active material obtained by the manufacturing method of the present invention, the coating film serving as the shell only needs to cover at least a portion of the surface of the positive electrode active material particles. The coating rate is not particularly limited, but by using the coating liquid of the present invention, for example, a coating rate exceeding 87% can be achieved, which can be 91.3% or more, 93.0% or more, or 96.4% or more.
[0067] The coating percentage can be calculated, for example, by XPS measurement. As a specific calculation method, the method described in the [Coating Percentage Measurement] section of the embodiments described later can be cited.
[0068] 3. Solid-state battery manufacturing methods
[0069] In this invention, a method for manufacturing a solid-state battery is provided. The solid-state battery includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer. The method for manufacturing the solid-state battery includes the following steps: the positive electrode layer is formed in a layered manner to contain at least a positive electrode composite material coated with a positive electrode active material obtained by the above-described method for manufacturing a positive electrode active material coated with a positive electrode active material.
[0070] The coated positive electrode active material provided by this invention can be used as a positive electrode active material constituting the positive electrode of a solid-state battery (such as a lithium-ion battery). By using the coated positive electrode active material of this invention in a solid-state battery, the rate of increase in resistance during charging and discharging of the solid-state battery can be reduced.
[0071] Furthermore, in this invention, a solid-state battery refers to a battery that includes a solid electrolyte. A solid-state battery can be a semi-solid-state battery containing both a solid electrolyte and liquid materials, or it can be a fully solid-state battery that does not contain liquid materials.
[0072] The manufacturing method of the solid-state battery of the present invention will be described below.
[0073] The positive electrode has a positive electrode layer and, if necessary, a positive electrode current collector.
[0074] The positive electrode layer is a layer containing at least the aforementioned coated positive electrode active material as the positive electrode active material. Furthermore, the positive electrode layer may, as needed, contain at least one of a solid electrolyte, a conductive material, and a binder.
[0075] In the manufacturing method of the present invention, the positive electrode layer includes a step of forming a positive electrode composite material in a layered manner, containing at least one positive electrode active material obtained by the manufacturing method of the present invention described above. That is, it includes a step of forming the positive electrode composite material in a layered manner, containing at least one of the above-described positive electrode active material, a solid electrolyte, a conductive material, and a binder as needed. Specifically, for example, a method can be used to prepare a positive electrode composite material (positive electrode slurry) by mixing the above-described positive electrode active material, solid electrolyte, conductive material, binder, and solvent, coating the positive electrode composite material onto a positive electrode current collector, and drying it. The positive electrode composite material can be subjected to ultrasonic dispersion treatment based on an ultrasonic homogenizer or the like.
[0076] Examples of solvents suitable for use in cathode composite materials include butyl acetate, butyl butyrate, heptane, and N-methyl-2-pyrrolidone. Examples of coating methods for cathode composite materials include blade coating, metal mask printing, electrostatic coating, dip coating, spray coating, roller coating, gravure coating, and screen printing. Known methods can be used to dry the cathode composite material; for example, a heating plate can be used.
[0077] Materials that can be used as positive current collectors include, for example, SUS, aluminum, nickel, iron, titanium, and carbon. The shape of the positive current collector is not particularly limited and can be various forms such as foil or mesh.
[0078] The content of the coated positive electrode active material in the positive electrode layer can be, for example, 40 to 95% by mass when the total mass of the positive electrode layer is set to 100% by mass. The positive electrode layer may contain positive electrode active materials other than the coated positive electrode active materials mentioned above.
[0079] Examples of conductive materials include, for example, carbon-based conductive materials, metal particles, and conductive polymers. Examples of carbon-based conductive materials include, for example, acetylene black (AB), Ketjen black (KB), fumed carbon fiber (VGCF), carbon nanotubes (CNT), and carbon nanofibers (CNF). The content of the conductive material in the positive electrode layer can be, for example, 0.1 to 5.0% by mass when the total mass of the positive electrode layer is set to 100% by mass.
[0080] As a solid electrolyte, for example, sulfide-based solid electrolytes, oxide-based solid electrolytes, halide-based solid electrolytes, and gel electrolytes can be used.
[0081] Sulfide solid electrolytes are electrolytes containing sulfur (S). They typically contain at least lithium (Li) and sulfur (S). Sulfide solid electrolytes may also contain nitrogen (M) (M is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In). Furthermore, sulfide solid electrolytes may contain halogen elements such as sulfur (F), chlorine (Cl), br, and iron (I).
[0082] Sulfide solid electrolytes can be glass-based (amorphous), glass-ceramic, or crystalline. Sulfide solid electrolytes can possess crystalline phases. Examples of such crystalline phases include the Thio-LISICON type, the Alger-Rodet type, and the LGPS type.
[0083] The composition of sulfide solid electrolytes is not particularly limited. Examples include xLi₂S·(1-x)P₂S₅ (0.5 ≤ x < 1) and yLiI·zLiBr·(100-yz)(xLi₂S·(1-x)P₂S₅) (0.5 ≤ x < 1, 0 ≤ y ≤ 30, 0 ≤ z ≤ 30). In these compositions, x can satisfy 0.7 ≤ x ≤ 0.8. Furthermore, another example of a sulfide solid electrolyte composition is Li₂S·(1-x)P₂S₅ (0.5 ≤ x < 1, 0 ≤ y ≤ 30, 0 ≤ z ≤ 30). 7-x PS 6-x X x X is at least one of F, Cl, Br, and I, and x satisfies 0 ≤ x < 2. Furthermore, Li can be cited as another example of a sulfide solid electrolyte composition. 4-x Me 1-x P x S4 (0 < x < 1). Me is at least one of Al, Zn, In, Ge, Si, Sn, Sb, Ga, and Bi. Examples of sulfide solid electrolytes include LiI-LiBr-Li3PS4, LiI-LiBr-Li2S-P2S5, LiI-Li2S-P2S5, LiI-Li2S-P2O5, and LiI-Li3PO4-P2S5.
[0084] The content of solid electrolyte in the positive electrode layer, such as the ratio of positive electrode active material to solid electrolyte (positive electrode active material / solid electrolyte), can be in the range of 6 / 4 to 8 / 2 by volume.
[0085] Examples of adhesives include styrene-butadiene rubber (SBR), polyimide (PI), polyacrylic acid (PAA), acrylonitrile-butadiene rubber (NBR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), styrene-isoprene-styrene block copolymer (SIS), and ethylene-propylene-diene copolymer (EPDM).
[0086] The content of the binder in the positive electrode layer can be, for example, 0.3% to 15% when the total mass of the positive electrode layer is set to 100%.
[0087] The negative electrode has a negative electrode layer and, if necessary, a negative electrode current collector.
[0088] The negative electrode layer is a layer containing at least a negative electrode active material. Furthermore, the negative electrode layer may, as needed, contain at least one of an electrolyte, a conductive material, and a binder.
[0089] The negative electrode active material can be in particle or sheet form. The average particle size of the negative electrode active material can be, for example, 1 μm to 30 μm. The negative electrode active material can include at least one material selected from the group consisting of carbon-based active materials, Li-based active materials, Si-based active materials, Si-C composite materials, and lithium titanate.
[0090] Carbon-based active materials may include at least one material selected from the group consisting of graphite, soft carbon, and hard carbon. "Graphite" is a general term for both natural and artificial graphite. Li-based active materials may include, for example, Li, Li silicates, and Li alloys. Si-based active materials may include, for example, Si, SiO, and Si alloys. Si-C composite materials refer to composite materials composed of carbon-based active materials (such as graphite) and Si-based active materials (such as Si).
[0091] Regarding the electrolyte, conductive material, and adhesive used in the negative electrode layer, the same materials as those described in the positive electrode layer can be cited.
[0092] Materials used as negative electrode current collectors include, for example, SUS, aluminum, copper, nickel, iron, titanium, and carbon. The shape of the negative electrode current collector can be foil-like or plate-like.
[0093] There are no particular limitations on the method of forming the negative electrode. For example, a negative electrode layer can be stacked on the negative electrode current collector by coating a negative electrode composite material containing negative electrode active material, other components and solvent onto the negative electrode current collector and then drying it.
[0094] The solid electrolyte layer is a layer formed between the positive electrode layer and the negative electrode layer, and contains at least a solid electrolyte, and may contain binders, etc., as needed.
[0095] Materials that are the same as those that can be contained in the aforementioned positive electrode layer can be used as the solid electrolyte and binder. When the total mass of the solid electrolyte layer is set to 100% by mass, the content of the solid electrolyte in the solid electrolyte layer can, for example, be in the range of 70% by mass or more and 100% by mass or less. The solid electrolyte layer may contain less than 1% by mass of electrolyte relative to the total mass of the solid electrolyte layer. When the total mass of the solid electrolyte layer is set to 100% by mass, the content of the binder in the solid electrolyte layer can, for example, be 0% by mass to 10% by mass.
[0096] Solid electrolyte layers can be formed, for example, by coating and drying a solid electrolyte composite material containing a solid electrolyte, a binder, and a solvent.
[0097] Solid-state batteries can be obtained by stacking a positive electrode, a negative electrode, and a solid electrolyte layer, with a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer. The stack of the positive electrode, solid electrolyte layer, and negative electrode can be pressurized in the stacking direction as needed.
[0098] There are no particular limitations on the types of solid-state batteries, but lithium-ion batteries are a typical example. Solid-state batteries can take various shapes, such as button cell, laminated cell, cylindrical cell, and prismatic cell. Furthermore, solid-state batteries can be either primary or secondary batteries. Applications of solid-state batteries include powering hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), battery electric vehicles (BEVs), gasoline vehicles, and diesel vehicles. Specifically, they can be used as power sources for driving hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and battery electric vehicles (BEVs). Solid-state batteries can also be used as power sources for mobile bodies other than vehicles (e.g., railways, ships, and aircraft) and for electrical products such as information processing devices.
[0099] Example
[0100] [Preparation of the coating liquid]
[0101] (Comparative Example 1)
[0102] An aqueous solution was obtained by dissolving 1.08 parts by mass of sodium pyrophosphate (Thermo Scientific) in 33.19 parts by mass of ion-exchanged water. Furthermore, to increase the molecular weight C of boron... B relative to the amount of phosphorus C P The ratio of "C" B / C P "To achieve a concentration of 1.0, a specified amount of boric acid (manufactured by NACALAI TESQUE, INC.) is dissolved in an aqueous solution. Finally, to increase the molecular weight of lithium C..." Li relative to the amount of phosphorus C P With boron, the amount of substance C B The ratio of the sum of C Li / (C P +C B The coating liquid was prepared by adding a specified amount of lithium hydroxide 1-hydrate (manufactured by FUJIFILM Wako Pure Chemical Corporation) to a concentration of 0.9 and dissolving it.
[0103] (Example 1)
[0104] An aqueous solution was obtained by dissolving 1.08 parts by mass of sodium tripolyphosphate (manufactured by Kanto Chemical Co., Inc.) in 35.55 parts by mass of ion-exchanged water. Otherwise, a coating solution was prepared in the same manner as in Comparative Example 1.
[0105] (Example 2)
[0106] An aqueous solution was obtained by dissolving 1.08 parts by mass of acidic sodium hexametaphosphate (manufactured by RINKACHEMICAL INDUSTRY CO.,LTD.) in 47.42 parts by mass of ion-exchanged water. Otherwise, a coating solution was prepared in the same manner as in Comparative Example 1.
[0107] (Example 3)
[0108] An aqueous solution was obtained by dissolving 1.08 parts by mass of metaphosphoric acid (manufactured by FUJIFILM Wako PureChemical Corporation) in 45.92 parts by mass of ion-exchanged water. Otherwise, a coating solution was prepared in the same manner as in Comparative Example 1.
[0109] [Raman Spectroscopy]
[0110] The coating solutions from Examples 1-3 and Comparative Example 1 were sealed in glass bottles and subjected to spectrophotometry using a Thermo Fisher Scientific Inc. DXR3xi imaging micro-Raman spectroscopy. The spectrophotometry conditions were as described in "1. Coating Solution" above. The results are shown below. Figure 1 middle.
[0111] according to Figure 1 The Raman spectra shown confirm that the coating liquids of Examples 1-3 reach a wavelength of 980 cm⁻¹. -1 Nearby and 1025cm -1 A peak value was observed nearby. On the other hand, the coating liquid of Comparative Example 1 was confirmed to have a peak value at 980 cm⁻¹. -1 It has a peak nearby, but at 1025cm -1 There are no peak values nearby.
[0112] Based on the obtained Raman spectrum, calculate 980 cm⁻¹. -1 Peak area I near the peak 980 and 1025cm -1 Peak area I near the peak 1025 And calculated I 1025 Compared to I 980 The ratio. The results are shown in Table 1.
[0113] [Preparation of coating positive electrode active material]
[0114] First, positive electrode active material particles were dispersed in the coating solutions of Examples 1-3 and Comparative Example 1 prepared above to form a slurry. NCA (LiNi) was used as the positive electrode active material particles. 0.81 Co 0.15 Al 0.04 O2). The solids concentration of each slurry is 69% by mass.
[0115] Next, the above slurries were spray-dried using a spray drying device (BUCHI Mini Spray Dryer B-290) (air supply temperature 200°C, air supply volume 0.45 m³ / h). 3 The surface of the positive electrode active material particles was coated with a coating liquid ( / min). Then, it was heat-treated at 200°C for 5 hours in an atmospheric atmosphere to obtain the coated positive electrode active material.
[0116] [Coverage Rate Measurement]
[0117] The surface elements of the various coated positive electrode active materials obtained above were analyzed using X-ray photoelectron spectroscopy (XPS). Specifically, narrow-scan analysis was performed using an XPS apparatus (ULVAC-PHI, Inc., PHI X-tool) with a path energy of 224 eV. The measured data were processed using analytical software (ULVAC-PHI, Inc., MultiPak), and the elemental ratios were calculated based on the intensity ratios of the detected peaks for C1s, O1s, P2p, Ni2p3, Co2p3, Al2p, and B1s. The coating percentage [%) of the coated positive electrode active material was calculated using the following formula. The results are shown in Table 1.
[0118] Coverage percentage = (P+B) / (P+B+Ni+Co+Al)×100%
[0119] In the above formula, P, B, Ni, Co, and Al represent the ratios of each element.
[0120] [Battery Review]
[0121] First, a positive electrode slurry was prepared by mixing the above-mentioned coated positive electrode active material, sulfide solid electrolyte (10LiI-15LiBr-75Li3PS4), conductive material (VGCF), binder (SBR), and dispersion medium (heptane). In the positive electrode slurry, the mixing ratio of the coated positive electrode active material to the sulfide solid electrolyte was set at a volume ratio of coated positive electrode active material / sulfide solid electrolyte = 7 / 3. The amounts of conductive material and binder were each set at 3 parts by mass relative to 100 parts by mass of the coated positive electrode active material. The positive electrode slurry was thoroughly stirred using an ultrasonic homogenizer.
[0122] Next, the positive electrode slurry was coated onto the surface of the positive current collector (Al foil) and dried to create a positive electrode sheet with a positive electrode layer formed on the positive current collector. The positive electrode slurry was dried at 100°C for 30 minutes using a heating plate. The positive electrode sheet was then cut into 1cm pieces. 2 It is disc-shaped.
[0123] Next, within the cylindrical fixture, a laminate was formed consisting of a disk-shaped positive electrode, a solid electrolyte layer containing a sulfide solid electrolyte, and a negative electrode layer containing a negative electrode active material (graphite) and a sulfide solid electrolyte, stacked sequentially. The same type of sulfide solid electrolyte was used in both the solid electrolyte layer and the negative electrode layer. A power generation element was formed by pressurizing the laminate, and terminals were connected to the power generation element, thereby fabricating an evaluation battery (all-solid-state battery).
[0124] The evaluation battery was adjusted to 40% SOC and discharged at a current rate of 2.5C for 5 seconds. The battery resistance (initial resistance) was calculated using the following formula. The results are shown in Table 1.
[0125] R=ΔV / I
[0126] R: Battery resistance
[0127] ΔV: Voltage drop during 5 seconds of discharge
[0128] I: Discharge current
[0129] After measuring the initial resistance, charge-discharge cycles were repeated at 60°C and a current rate of 1.0C. After 100 cycles, the battery resistance (resistance after durability) was calculated again under the same conditions using the above formula. The results are shown in Table 1.
[0130] Based on the initial resistance and the resistance after durability calculated above, the resistance increase rate was calculated using the following formula. The resistance increase rate is displayed as a percentage (%). The results are shown in Table 1.
[0131] ΔR = (R1 - R0) / R0 × 100
[0132] ΔR: Rate of increase in resistance
[0133] R0: Initial resistance
[0134] R1: Resistor after durability
[0135] [Table 1]
[0136]
[0137] As shown in Table 1, when using Raman spectra at 980 cm⁻¹ -1 It has a peak value nearby, but at 1025cm. -1 In the case of the coating liquid of Comparative Example 1, which does not have a peak value nearby, the coverage rate is 86.5% and the resistance increase rate is 69.3%.
[0138] In contrast, when using Raman spectroscopy at 980 cm⁻¹ -1 Nearby and 1025cm -1 In the case of the coating solutions of Examples 1-3, which exhibit peak values at two nearby locations, the coverage ratio increases to 91.3%-96.4%, and the resistance increase rate decreases to 42.6%-56.0%. A low resistance increase rate indicates high cycle performance and stable battery characteristics over a long period. Furthermore, in the coating solutions of Examples 1-3, the peak area I... 1025 Relative to peak area I 980 The ratio (I) 1025 / I 980The resistance is in the range of 0.3 or higher and 8.8 or lower. In Example 2, which contains acidic hexametaphosphate (Na) as an acidic hexametaphosphate compound, it was found that not only was the rate of increase in resistance low, but the initial resistance value was also low.
Claims
1. A coating liquid comprising a solvent and a solute containing a phosphoric acid compound, characterized in that, The coating liquid exhibits a Raman spectrum at 980 cm⁻¹. -1 Nearby and 1025cm -1 Peak values are found in the vicinity.
2. The coating liquid according to claim 1, characterized in that, The coating liquid contains Li and B. The coating liquid is at 1025cm -1 Peak area I near the peak 1025 Relative to the 980cm -1 Peak area I near the peak 980 The ratio of I 1025 / I 980 It is in the range of 0.3 or higher and 8.8 or lower.
3. The coating liquid according to claim 1, characterized in that, The phosphoric acid compound includes an acidic hexametaphosphate compound.
4. A method for manufacturing a coated positive electrode active material, characterized in that, The manufacturing method includes the following steps: A mixture is prepared by mixing positive electrode active material particles and the coating liquid according to claim 1; and The coated positive electrode active material is manufactured by drying the mixture. The coated positive electrode active material comprises positive electrode active material particles and a coating film. The coating film covers at least a portion of the surface of the positive electrode active material particles.
5. A method for manufacturing a solid-state battery, the solid-state battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, the method for manufacturing the solid-state battery being characterized by comprising the following steps: The positive electrode layer is formed in a layered manner as a positive electrode composite material containing at least the positive electrode active material coated by the manufacturing method of claim 4.
Citation Information
Patent Citations
Coating liquid, composite particle manufacturing method, composite particle, and all-solid-state battery
JP2023122182A
Composite particle, positive electrode, all-solid-state battery, and manufacturing method of composite particle
JP2023136753A